Long-Term Suppressive Therapeutic-Drug-Monitoring-Guided Dalbavancin Therapy for Cardiovascular Prosthetic Infections - Altea Gallerani; Milo Gatti; Andrea Bedini; Stefania Casolari; Gabriella Orlando; Cinzia Puzzolante; Erica Franceschini; Marianna Menozzi; Antonella Santoro; Nicole Barp; Sara Volpi; Alessandra Soffritti; et al. (MDPI AG, 2023)
Dalbavancin represents a promising treatment for cardiovascular prosthetic infections due to its prolonged half-life, bactericidal activity, large spectrum of activity, and excellent biofilm penetration. However, the use of dalbavancin in this setting is limited, and only a few cases have performed therapeutic drug monitoring (TDM) analysis to optimize dosage in suppressive treatments longer than 4 weeks. Our retrospective case series reports the use of dalbavancin in a small cohort of patients with cardiovascular prosthetic infections (cardiac implantable electronic device infections (CEDIs), prosthetic valve endocarditis (PVE), prosthetic vascular graft infections (PVGIs)) treated with dalbavancin as sequential therapy. From May 2019 to May 2023, 14 patients were included: eight cases of PVE (57.1%), seven cases of PVGI (50%), three cases of CEDI (21.4%), and four cases with overlap of infection sites (28.6%). The main pathogen was Staphylococcus aureus (35.7%). Prosthesis replacement was obtained in four patients (28.6%). The median time between symptom onset and the end of treatment was 15 weeks (IQR 7-53), with a median duration of dalbavancin therapy of 8 weeks (IQR 1 to 45 weeks) and 3.5 doses per patient. Among patients managed with TDM-guided strategy, dalbavancin infusion intervals ranged from 4 to 9 weeks. The median length of follow-up was 65 weeks (IQR 23 to 144 weeks). Clinical success was achieved in 10 cases (76.9%); all clinical failures occurred in patients with the implant retained. Among patients monitored by TDM, clinical success was 87.5% vs. 60% in patients treated without TDM. Because of pharmacokinetic individual variability, dalbavancin TDM-guided administration could improve clinical outcomes by individualizing dosing and selecting dosing intervals. This case series seems to suggest a promising role of long-term suppressive dalbavancin treatment for difficult-to-treat cardiovascular prosthesis infection, also with limited surgical indications.